Bladder mucosal smoothness predicts early recovery of urinary continence after laparoscopic radical prostatectomy - Le Yu; Ye Yan; Hongling Chu; Shaohui Deng; Jianfei Ye; Guoliang Wang; Yi Huang; Fan Zhang; Shudong Zhang (BMC Urology)
Abstract Background To propose the bladder mucosal smoothness (BMS) grade and validate a predictive model including MRI parameters preoperatively that can evaluate the early recovery of urinary continence (UC) after laparoscopic radical prostatectomy (LRP). Methods A retrospective analysis was conducted on 203 patients (83 patients experienced UI at the three-month follow-up) who underwent LRP in our medical center and were diagnosed with prostate cancer (PCa) from June 2016 to March 2020. Patients’ clinicopathological data were collected. Prostate volume (PV), membranous urethra length (MUL), intravesical prostatic protrusion length (IPPL), and BMS grade were measured by MRI. The total sample was randomly divided into a training set (n = 142) and a validation set (n = 61). A model was developed to predict the risk of urinary incontinence (UI) at three months after LRP. Results Age group, clinical T stage group, BMS grade group, PV group, IPPL group, and MUL group differed significantly between patients in the UI group and the UC group (all P values < 0.05). Multivariate analysis identified 3 MRI-related predictors selected for the prediction model: BMS grade (1 odds ratio [OR] 0.17, 95% CI 0.11–0.66; P value = 0.024) (2 + 3 OR 0.17, 95% CI 0.04–0.66; P value = 0.011), IPPL (> 5 mm OR 0.17, 95% CI 0.1–0.64; P = 0.004), and MUL (≥ 14 mm OR 6.41, 95% CI 2.72–15.09; P value < 0.001). The model achieved a highest area under the curve of 0.900 in the training set and the validation set. The sensitivity and specificity of the prediction model were 0.800 and 0.816. Conclusion Our study confirmed that patients with lower BMS grade are associated with early recovery of urinary continence after LRP. A prediction model was developed and validated to evaluate the early recovery of urinary continence after LRP. Clinical trial number Not applicable.